Research and higher education policies for transforming societies : perspectives from Latin America and the Caribbean : selected proceedings - Mollis, Marcela (UNESCO ParisFR, 2007)
Focuses on building research capacity, enhancing research productivity and ensuring the relevance and utility of research. Deals with the renewal of higher education and science systems to meet the challenges of knowledge-based societies, as well as the Millennium Development Goals.